Whole-body control of anticipated and unanticipated sidestep manoeuvres in female and male team sport athletes. Issue 19 (2nd October 2019) - Wyatt, Hannah; Weir, Gillian; van Emmerik, Richard; Jewell, Carl; Hamill, Joseph
ABSTRACT: The purpose of this study was to investigate the influence of sex and planning time on spatial and temporal aspects of the whole-body centre of mass (CoM) mechanics during sidestepping performance. Seventeen female and 17 male collegiate team sport athletes completed seven anticipated and seven unanticipated sidestep trials during which three-dimensional CoM data were recorded. Female athletes had a reduced ability to reorient their CoM towards the desired direction of travel (lower medio-lateral and anterior-posterior CoM velocity) than their male counterparts, with reduced medial (closer to stance foot) and increased posterior positioning of CoM relative to the stance foot (p < 0.05). When planning time was limited, female and male athletes performed sidestepping with CoM further from the stance foot (more medial) and more anterior than in the anticipated condition (p < 0.05) at reduced medio-lateral velocities. Sex and condition control strategy differences were evident both in the preparatory phase and the stance phase. The current research draws attention to the foreseen benefits of training athletes, with particular emphasis on females, to direct CoM towards the desired direction of travel in the preparatory and stance phases within temporally constrained situations for improved performance.